Characteristics of inmates witnessing overdose events in prison: implications for prevention in the correctional setting - Feal Jacqueline; Hernández-Viver Adriana; Albizu-García Carmen E; Rodríguez-Orengo José F (BMC, 2009)
Abstract Background Although prevention of opiate overdose has been gaining attention as a harm reduction measure with community drug users, there is scarce information about drug overdose in prison. In correctional institutions without a drug free environment, awareness of overdose events is an important public health concern. This study explores the frequency with which inmates in a state penitentiary system report having witnessed drug overdose events in prison. It also explores whether participants who have witnessed an overdose in prison and know someone who died from an overdose in prison significantly differ from those that do not in selected sociodemographic variables and drug use history to identify a target population for prevention interventions. Methods Data comes from a cross-sectional survey of sentenced inmates in the state prisons of Puerto Rico. A complex probabilistic, multistage sampling design was used. A total of 1,179 individuals participated for an 89% response rate. Results Factors associated with witnessing an overdose event in prison include: male sex, age 25 or older, drug use during current incarceration, and drug injection in prison. Factors associated with knowing someone who died from an overdose in prison include: male sex, age between 25-35, previous incarcerations, and drug use during current incarceration. Conclusion Witnessing a drug overdose is a frequent occurrence within the prison system. The likelihood of witnessing an overdose is greater with being male, polydrug use and drug injection in prison. Findings signal an urgent public health challenge that requires prompt interventions to reduce this drug related harm within the correctional system, including adequate access to medication with opiate agonists.